Efficiency enhancement of natural cocktail dyes in a TiO2-based dye-sensitized solar cell and performance of electron kinetics on the TiO2 surface - Dhanasekaran, P.; Marimuthu, R. (Frontiers in Energy Research, 2023)
In this study, natural dye extracts were prepared from the dried leaves of Andrographis paniculata and Psidium guajava (APPG). The study’s objective was to increase the light harvesting phenomenon from solar energy utilizing natural dye from APPG, and the problem statement was to harvest the optimum solar radiation and convert it into electrical energy. Acetone and ethanol were used as solvents during the preparation process. Based on this research, the crystallite size of TiO2 nanoparticles was assessed, the impact of acetone and ethanol on APPG dye was compared, and the absorption, FTIR, and UV-Vis spectra of the solar cell fabrication process using solvents were experimentally explored. APPG leaf extract functions as a dye sensitizer. Cells are precisely sandwiched with a photoanode, TiO2 nanoparticles, an electrolyte (I/I3−), and a cathode. The JV properties of dye extracts utilizing acetone and ethanol were measured using a solar simulator equipped with a 100 mW/cm2 Xenon light and a Keithley 2400 Graphical Series SMU. An experimental DSSC with dye extraction and utilizing acetone solvent yielded a maximum photo-conversion efficiency of 0.6914%, while ethanol yielded a photo-conversion efficiency of 0.5630%. Furthermore, an energy-level diagram was used to explain the electron kinetics of DSSC, and the time required for transfer electron injection in the TiO2 surface from a dye-excited state was 150 ps.